THE ROLE OF GOOD FINANCIAL RECORDS ON THE PROGRESS OF BANDAR LAMPUNG STREET VENDOR BUSINESS - Abram Radiva Suroso; Ardansyah (ZILLZELL MEDIA PRIMA, 2024)
MSMEs have become a very important sector in the Indonesian economy. One of them is included in the type of MSMEs that refer to micro, small, and medium enterprises which are often identified with the term street vendors or abbreviated as street vendors. In running a business, the important thing to do and apply is financial recording. Good financial records become capital in good business management in order to achieve success in their business. This study aims to measure the extent to which the involvement of street vendors around the governor's office field (Jl. Wolter Monginsidi, Teluk Betung Utara, Bandar Lampung) understands and implements good financial records in their business. This research applies a qualitative approach and uses case studies as a research method. Data collection is done through interviews, observation, and documentation. The data analysis used is qualitative descriptive analysis. From the findings of the research that has been conducted, street vendors who carry out trading activities around the governor's office field (Jl. Wolter Monginsidi, Teluk Betung Utara, Bandar Lampung) do not understand and apply good financial records in their business. Limited knowledge about good financial records is an obstacle for traders to implement good financial records.